Martian Water Ice Clouds During the 2018 Global Dust Storm as Observed by the ACS‐MIR Channel Onboard the Trace Gas Orbiter. Issue 3 (11th March 2020) - Stcherbinine, A.; Vincendon, M.; Montmessin, F.; Wolff, M. J.; Korablev, O.; Fedorova, A.; Trokhimovskiy, A.; Patrakeev, A.; Lacombe, G.; Baggio, L.; Shakun, A.
Abstract: The Atmospheric Chemistry Suite (ACS) instrument onboard the ExoMars Trace Gas Orbiter (TGO) European Space Agency‐Roscosmos mission began science operations in March 2018. ACS Mid‐InfraRed (MIR) channel notably provides solar occultation observations of the Martian atmosphere in the 2.3‐ to 4.2‐ μ m spectral range. Here, we use these observations to characterize water ice clouds before and during the MY 34 Global Dust Storm (GDS). We developed a method to detect water ice clouds with mean particle size ≤ 2  μ m and applied it to observations gathered between L s = 16 5 ∘ and L s = 24 3 ∘ . We observe a shift in water ice cloud maximum altitudes from about 60 km before the GDS to above 90 km during the storm. These very high altitude, small‐sized ( r eff ≤ 0 . 3 μ m) water ice clouds are more frequent during MY 34 compared to non‐GDS years at the same season. Particle size frequently decreases with altitude, both locally within a given profile and globally in the whole data set. We observe that the maximum altitude at which a given size is observed can increase during the GDS by several tens of kilometers for certain sizes. We notably notice some large water ice particles ( r eff ≥ 1 . 5 μ m) at surprisingly high altitudes during the GDS (50–70 km). These results suggest that GDS can significantly impact the formation and properties of high‐altitude water ice clouds as compared to the usual perihelion dust activity. Plain Language Summary: In this article, we use data from the Atmospheric Chemistry Suite infrared spectrometer onboard the European Space Agency‐Roscosmos ExoMars Trace Gas Orbiter mission to study water ice clouds in the Martian atmosphere. More specifically, we aim to characterize the evolution of their altitude, geographic distribution, and microphysical properties before and during the planet‐wide dust storm that occurred during the summer of 2018. In particular, we developed a method to simultaneously detect the water ice clouds and constrain their particle size using simulated spectra of water ice. We observe that the maximal altitude of the clouds increased from 60 km to above 90 km during the storm. Most high‐altitude clouds have small particle sizes (lower than 0.3  μ m) as expected from the low pressure at such altitude. However, we also observe for the first time large (larger than 1.5  μ m) water ice particles at unusually high altitude (higher than 60 km), uniquely during the storm. This suggests that the increased atmospheric activity associated with global dust storm significantly impacts water ice cloud formation. Key Points: Monitoring of Martian water ice clouds and derivation of vertical profiles of particle size using the 3‐ μ m spectral band Observation of mesospheric water ice clouds at altitudes greater than 90 km during the MY 34 GDS Evidence of water ice particles larger than 1.5  μ m between 50 and 70 km during the GDS